Challenges in the management of floating knee injuries: Results of treatment and outcomes of 224 consecutive cases in 10 years. (August 2019) - Rollo, Giuseppe; Falzarano, Gabriele; Ronga, Mario; Bisaccia, Michele; Grubor, Predrag; Erasmo, Rocco; Rocca, Guido; Tomé-Bermejo, Felix; Gómez-Garrido, David; Pichierri, Paolo; Rinonapoli, Giuseppe; Meccariello, Luigi
Highlights: The floating knee is a devastating traumatic pathology for the survival and quality of life of the patient. Many are the comorbidities associated with the floating knee that put the patient's life at risk. The early stabilization of both fractures improves outcomes. Subjective and objective outcomes can be satisfactory after years and numerous trauma surgeries. The current Floating Knee classifications in use are not discriminating or prognostic. Abstract: Introduction: Floating knee is a flail knee joint resulting from fractures of the shafts or adjacent metaphyses of the femur and the ipsilateral tibia. It is usually associated with several complications and mortality. This study was designed to present our experience with the treatment of this injury. Material and method: This study was performed between January 2004 and December 2014. 224 cases of floating knee injuries gathered from the 34, 480 lower extremities trauma files were studied, and the target information recorded. The injuries most frequently occurred in subjects between 16 and 35 years of age (60.71%), and in male subjects (85.71%). The most frequent mechanism of injury was traffic accident (92.85%). External fixation was the common type of treatment (82.14%) in emergency or as a definitive treatment. The treatment was performed within 24 h of the trauma. We performed a 36-month follow up with clinical examination, radiographs, assessing the complications, and using the Modified Cincinnati Rating System Questionnaire (MCRSQ) and the Karlström/Olerud Score (KOS) to evaluate the progression of the outcomes. Results: Early complications included 8 cases of compartment syndrome, 60 open fractures and 24 partially amputated limbs. A total amputation was performed in 3 patients. The most common late complication was heterotopic calcifications of the knee ( n  = 68, 30.6%). Good scores for MCRSQ and KOS were obtained only after patients were sent to a reference center for knee surgery. Conclusions: Our experience revealed that the complication rate associated with floatingknee injuries remains high, regardless of the performed treatment. Surgeons should focus on reducing complications while treating these severe injuries.